Employer Perceptions of Physical Therapists' Residency and Fellowship Training: Insights for Career Development Planning. Issue 1 (March 2019) - Briggs, Matthew S.; Whitman, Julie; Olson-Kellogg, Becky; Farrell, Joseph; Glaws, Kathryn R.; Walker, Joann M.; Clutter, Jill; Tichenor, Carol Jo
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Residencies and fellowships have been developed to train physical therapists (PTs) toward advanced expertise while emphasizing patient outcomes, evidence-based care, and advancing practice. Research evaluating the impact of PT residency or fellowship training, its value, and/or benefits is scarce. The purpose of this study was to evaluate if employers perceive the performance of residency- and/or fellowship-trained employees differently than non–residency-trained and/or non–fellowship-trained employees. Methods: Participants were employers who employ PTs who have graduated from accredited physical therapy residency and fellowship programs in the United States. A survey was distributed asking perceptions of how employees, who were residency and/or fellowship trained, performed compared to employees with equivalent years of experience who were not residency or fellowship trained. Mann–Whitney U tests were used for comparison. Results: A total response rate of 40% ( n = 226) was achieved, and a total of 184 responses were included. Respondents rated residency- and/or fellowship-trained employees higher in domains of Leadership, Communication, Clinical Aptitude, Scholarship/Evidence Based Practice, and Teaching when compared to experienced-matched colleagues. Employers rated fellowship-trained employees higher than residency-trained employees in areas of Leadership, Communication, and Clinical Aptitude. Discussion and Conclusion: These results may be important for assisting students and early- and mid-career professionals in making decisions about whether to attend residency and/or fellowship education and for understanding what employers value in making hiring decisions. Further, these considerations may influence future promotion opportunities, patient satisfaction, and payment policies.